Autonomy: the next phase of dialogue between systemic functional linguistics and Legitimation Code Theory. (4th May 2020) - Maton, Karl; Howard, Sarah K.
ABSTRACT: Systemic functional linguistics (SFL) has long enjoyed a close and fruitful dialogue with Legitimation Code Theory (LCT). A growing number of scholars enact both theories together in empirical research to explore how knowledge and language relate together to shape practice. This work both generates greater explanatory power in research and encourages conceptual advances in each of the two theories. In this paper we introduce new concepts from a recently renovated dimension of LCT called Autonomy that may spark a new phase of dialogue between the frameworks. We begin by summarising the existing ongoing phases of dialogue between LCT and SFL. We then introduce the concepts of "autonomy codes", which explore changing relations among different kinds of practices by tracing "autonomy pathways". The potential of these concepts for empirical research is illustrated through detailed analyses of classroom practice in which schoolteachers attempt to use everyday knowledge as ways of helping students learn History. These analyses suggest that "one-way trips" from one form of knowledge practice into another constrain knowledge-building while "autonomy tours" that engage with, repurpose and connect other knowledge practices support knowledge-building. Finally, we consider how these concepts might raise questions for SFL research and theory and thereby initiate a new phase in its dialogue with LCT.